User Engagement on Social Media: A Case Study of Online Buddhist Community Engagement Behaviour during the COVID-19 Pandemic in Malaysia - Lim Soo Jin; Cheah Shu Xu (Universitas Internasional Batam, 2023)
The COVID-19 pandemic has affected many countries, impacting almost every aspect of people’s lives. Religious organizations had to adapt by connecting with worshippers online. Social media platforms, in particular, were crucial in delivering religious teachings, practices, and activities to its online community. This study examines the motivational factors that drive young adults’ engagement in online Buddhist communities, adopting the social identity theory as a framework to understand why individuals portray individual or group-based behaviors in an online religious community. This study uses qualitative Internet-based in-depth interviews to investigate the online behavior of 21 members from the Buddha’s Light International Association Young Adults Division (BLIA YAD) Malaysia Facebook community during the pandemic. The participants comprise of 20 to 39-year-old adults who use social media as their primary source to obtain information on Buddhism and to communicate with other believers during this period. The findings revealed that the users perform specific engagement behaviors (like, share, and comment) based on varied reasons. The factors that drive users to “like” and “share” posts within the Buddhist online community include offline relationship, sense of belonging, sense of moral obligation, emotional connection, social support, trust, and personal identity. The implications of this study explores and reveals the motivations and behavior of faithful users with religious content. While most studies deal with the way users interact with commercial or public content this study explores the way the user interacts with religious content within the virtual space of a religious organization.